Upaya Pendampingan Awal Menuju Pembangunan TPS 3R Melalui Sosialisasi Pemilahan Sampah, Pemasangan Papan Edukasi, dan Penyediaan Tempat Sampah di Desa Gondang - Sri Purwanti; Adam Teguh Ramadhani; Lennyta Eka Rindi Agustin; Freddy Parsaulian Situmorang; Angga Kristandiyo; Zusa Ikhwanul Kirom; Ghofit Ferdi Alannazurin; Fahreza Senatrya Nugroho; Bheta Kusumawardani; Alifia Nazala Putri Agasia; Achmad Annas Rayhan; Zahra Haya Shabiyyah; Rahma Harianti Arofah; Intan Nur Asifah Al Mufidah; Ulil Marifatul Umana; Erick Kurniawan; Nur Vita Hasanah; Reza Nirmala; Marsella Ayu Muthia; Nia Amelia Antony; Kensa Febry Amanda; Ilham Hidayat; Alfiano Fandri Cartas; Dimas Fajar Wahyudi; Gumilar Jalasena Yudha; Nadya Taurisia (Lembaga Pengembangan Kinerja Dosen, 2026)
Household waste management in Gondang Village remains a major problem because waste is not sorted from the source and supporting facilities are still limited, resulting in mixed organic, inorganic, and residual waste, potentially polluting the environment. To support the planned development of a 3R Waste Management Site (TPS 3R) in 2026, a community service activity was conducted aimed at increasing community knowledge, awareness, and readiness regarding waste sorting and the application of the Reduce, Reuse, and Recycle concept. This activity used a participatory approach through outreach, waste sorting demonstrations, installation of educational boards on waste decomposition times, and the provision of separate trash bins in four hamlets. The results of the activity showed an increase in community understanding of waste types, 3R principles, and long-term environmental impacts, accompanied by positive responses and high enthusiasm. The educational boards and facilities provided served as visual reminders that encouraged behavioral change, making this activity an important first step in preparing the Gondang Village community towards sustainable waste management through the 3R Waste Management Site (TPS 3R).